Parallel worlds of divided community: time does not make much difference - Čorkalo Biruški, Dinka; Ajduković, Dean (2012)
Violent conflict can drive a wedge between individuals and ethnic groups that once used to be highly integrated, leaving the community divided in the post-conflict era. The members of two groups stay apart for a long time if there are no systemic efforts to repair social ties that make a community stable and functional. Schooling system has such a potential. After the 1991-1995 war, Croat and Serb children in the city of Vukovar in Croatia, started to go to separate schools. Language of teaching became the major line of division and the ground for perusing demands for minority education, making the issue of schooling highly controversial for those who advocate school integration and those who oppose it. We measured attitudes towards school integration and interethnic attitudes, contacts and discriminatory tendencies of Croat and Serb children in elementary and high schools in 2001 (N=718) and in 2008 (N=703). We demonstrated that without purposeful efforts that can bring the two groups closer, their polarized interethnic attitudes and behavioral intentions towards the outgroup stay basically unchanged over time, even when controlled for children's age and gender. Implications for further post-conflict interethnic community relations are discussed with emphasis on the role a school may have in this process.
Projekt MZOS
ENG